Evaluating the feasibility and predictive accuracy of biodynamic imaging to platinum-based chemotherapy response in esophageal adenocarcinoma - Ajrouch, Ali; Krempley, Ben; Karkash, Ahmad; Dewitt, John M.; Al-Haddad, Mohammad; Lim, Dawith; Nolte, David; Turek, John; Perkins, Susan M.; Jalal, Shadia I. (Frontiers in Oncology, 2024)
BackgroundEsophageal cancer management lacks reliable response predictors to chemotherapy. In this study we evaluated the feasibility and accuracy of Biodynamic Imaging (BDI), a technology that employs digital holography as a rapid predictor of chemotherapy sensitivity in locoregional esophageal adenocarcinoma.MethodsPre-treatment endoscopic pinch biopsies were collected from patients with esophageal adenocarcinoma during standard staging procedures. BDI analyzed the tumor samples and assessed in vitro chemotherapy sensitivity. BDI sensitivity predictions were compared to patients’ pathological responses, the gold standard for determining clinical response, in the surgically treated subset (n=18).ResultBDI was feasible with timely tissue acquisition, collection, and processing in all 30 enrolled patients and successful BDI analysis in 28/29 (96%) eligible. BDI accurately predicted chemotherapy response in 13/18 (72.2%) patients using a classifier for complete, marked, and partial/no-response. BDI technology had 100% negative predictive value for complete pathological response hence identifying patients unlikely to respond to treatment.ConclusionBDI technology can potentially predict patients’ response to platinum chemotherapy. Additionally, this technology represents a promising step towards optimizing treatment strategies for esophageal adenocarcinoma patients by pre-emptively identifying non-responders to conventional platinum-based chemotherapy.